Peluang dan Tantangan Penggunaan Blockchain Technology pada Perbankan Syariah di Indonesia - Rafiqi Ihsan (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The rapid development of technology will have a significant impact on the use of Blockchain technology in Islamic Banking. The aim of this research to find out the opportunities and challenges facing Islamic banking when applying Blockchain technology. This study uses qualitative methods. Authors use secondary data obtained from nationally and internationally accredited published papers as well as credible media articles. The results of this study explain that there are three main aspects that are opportunities as well as challenges faced by Islamic banking in the use of Blockchain technology; First, the development of Blockchain companies in the financial sector demands that human resource conditions have a capable ability in managing Blockchain in Islamic banking. Second, increased internet penetration and transactions in Blockchain systems require equalization of the internet and enlarged blocksize. Third, there need to be specific regulations from Bank Indonesia and Otoritas Jasa Keuangan related to the use of Blockchain technology in Islamic Financial Institutions, the optimization of secure data governance, and the availability of audit mechanisms.